Antidiabetic Activity of Methanol Extract of Bark of Alstonia scholaris from Papua - Nitya Praptiwi Nitya Praptiwi; Bertha Mangallo (Jurnal Natural, 2022)
One of the biological wealth that grows in Papua is Alstonia scholaris, known by the Maybrat tribe as the swe plant and is used as a traditional medicine for antidiabetic. The Swe tree contains a lot of white sap and tastes very bitter. There is also a bitter taste in the roots, bark, and leaves so it is thought to contain a lot of bioactive compounds of alkaloids which have the potential as antidiabetic. This study aims to extract and determine of antidiabetic activity by the inhibition activity of the α-glucosidase of methanol extract of bark of Alstonia scholaris from Papua as a basis for the development of antidiabetic drugs based on local resources. The method used was extraction by maceration, phytochemical screening test, inhibition activity of the α-glucosidase test and functional group analysis using FTIR. The results of phytochemical screening showed that methanol extract of bark of Alstonia scholaris from Papua was strongly positive containing secondary metabolites of alkaloids and flavonoids. Analysis of functional groups with FTIR showed that the secondary metabolite compound was thought to contain -OH functional group, C=C stretch and C=O group. IC50 value of Alstonia scholaris bark MeOH extract showed 0.97 µg/mL for α-glucosidase inhibition. This study suggest the methanol extract of bark of Alstonia scholaris might be considered as potential source of bio active constituents with excellent antidiabetic activity.